Mekanisme Penetapan Pajak Kendaraan Bermotor (PKB) Pada Kantor Bersama Samsat Palu - Sissy Anastasya; Adfiyani Fadjar; Wiri Wirastuti (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Motorized Vehicle Tax is a tax on ownership and/or control of motorized vehicles. In the implementation of the collection is carried out in the office with Samsat. The SAMSAT Joint Office involves three government agencies, namely: the Regional Revenue Agency, the Regional Police of the Republic of Indonesia, and PT. (Persero) Jasa Raharja Loss Insurance. The Technical Service Unit (UPT) Region 1 Palu SAMSAT has a work unit, namely the Billing and Determination Implementation Unit (PENTAP) which focuses on the billing section and determining the amount of tax bills to be raised. The method used in the preparation of this Final Project will be discussed descriptively regarding the Motor Vehicle Tax Determination Mechanism carried out by the Taxpayer Collection and Determination Unit at the SAMSAT Wil.1 Palu Office.